Observation of the fine structure of antennal sensilla of the stink bug, Eocanthecona furcellata (Hemiptera: Pentatomidae). (November 2021) - Zhao, Hang; Liang, Chen; Gao, Ping; Xie, Yong-hui; Wang, Zhi-jiang; Wu, Guo-xing; Tang, Guo-wen; Cheng, Bin; Gao, Xi
Graphical abstract: Highlights: The fine morphology, types, distribution and abundance of the sensilla on antennae of E. furcellata are investigated. Adult of E. furcellata has five types and thirteen subtypes of antennal sensilla . The type and abundance of sensilla was sexually dimorphic. Possible function of sensilla on E. furcellata are speculated. The work will provide information and reference for further research. Abstract: In order to explore the mechanism underlying chemosensation in Eocanthecona furcellata, the external morphology of its antennae and the type, quantity, distribution and ultrastructure of the sensilla were observed on both sexes of adults and 5th-instar nymphs using scanning electron microscopy. The results showed that the antennae of E. furcellata consisted of three parts: scape, pedicel and flagellum. There were five types of sensilla on the antennae, which included sensilla trichoidea (ST), sensilla chaetica (SCh), sensilla coeloconica (SCo), sensilla basiconica (SB) and squamifornia denticles (SD). Further, there were 4 subtypes of ST and SB and 2 subtypes of SCo and SCh. The number of sensilla on nymphs was significantly lower than that on adults. The antennae of adults showed sexual dimorphism, as the number of sensilla on female adults was higher than that on male adults. SB4 was found only on females and SCo2 was found only on males. These inter-sexual differences may be related to chemoreception of sex pheromone and chemical predation location. The morphology and putative functions of each sensilla were compared and discussed. These results provide a reference for further study of the behavioral biology, chemical ecology and electrophysiology of insects, and also provides a scientific basis for new ways of biological control.